Toward Teaching Methods that Develop Learning and Problem Solving Skills in Engineering Students - Loji, Kabulo (South African Journal of Higher Education, 2016)
Problem solving skills and abilities are critical in life and more specifically in the engineering field. Unfortunately, significant numbers of South African students who are accessing higher education are lacking problem solving skills and this results into poor academic performance jeopardizing their progress especially from first to second year. On the other hand, teaching problem solving to under-prepared first year learners is a challenge to academics that are required to think in innovative ways about teaching and learning strategies in order to respond in an efficient manner to South Africa’s high demand for quality engineering graduates. This paper discusses two successful sample lessons of how higher-order thinking skills can be integrated into the content of a so called “bottle-neck” subject namely Electrical Engineering 1 (EE1), with the goal of enhancing problem solving skills and consequently improve under-prepared learners’ performance. The importance of developing active student engagement practice as well as conceptual understanding is highlighted.